China's Engagement with the Sixteen Countries of Central, East and Southeast Europe under the Belt and Road Initiative. Issue 5 (September 2017) - Vangeli, Anastas
Abstract: This paper provides an overview of China's burgeoning relationship with Central, East and Southeast Europe (CESEE) in the context of the Belt and Road Initiative (BRI). China has rapidly expanded the extent of its interactions with CESEE since 2012, and this region has subsequently become one of the focal points of the BRI. The key feature of China's engagement with CESEE is the devising of an experimental and innovative approach, demonstrated in the establishment of an institutional mechanism for cooperation with a particular group of 16 CESEE countries (16+1). The case of China–CESEE relations offers an insight into how, in the era of the BRI, China is complementing its economic approach with institution‐building and policy coordination. The article concludes that as the BRI progresses, these tendencies will remain central to China's relations with CESEE.